Which impacts matter for pavement management decisions? Quantifying social sustainability based on a capability approach - Jessica Boakye; Egemen Okte (Transportation Research Interdisciplinary Perspectives)
This study addresses the need to evaluate the social sustainability of pavement management decisions, particularly during the use and maintenance stages. While Life Cycle Assessment (LCA) and Life Cycle Cost Analysis (LCCA) are well-established for assessing environmental and economic impacts, Social Life Cycle Assessment (S-LCA) remains understudied for pavements, especially within the context of pavement management. This research introduces a methodology using the Capability Approach to quantify social impacts, emphasizing their importance, relevance, and influenceability. The resulting framework provides a working list of key social impacts such as fatalities, bodily health, mobility, comfort, environmental emissions, financial impact, and equity. These impacts are particularly relevant during the use and maintenance stages of pavement life cycle, where management decisions directly affect road users and surrounding communities. A case study illustrates the application of this framework, analyzing pavement conditions and their social impacts on communities. This study offers a structured approach for integrating social sustainability into pavement management decisions.